Analysis of food‐energy‐water nexus based on competitive uses of stream flows of BeiChuan River in eastern QingHai‐Tibet Plateau, China. Issue 1 (3rd October 2017) - Zhao, Xia; Harbor, Jon; Engel, Bernie; Theller, Lawrence; Yu, Feng; Cao, GuangChao; Cui, YuXiang; Tang, WenJia; Zhang, MeiTing
Abstract : Rapid urbanization and industrial development in the eastern region of the Qinghai‐Tibetan Plateau is imposing significant and interdependent pressures on food, energy, and water. A long‐term assessment of the regional water balance reveals a complex interaction of factors that are altering the available water, including changes in the locally grown food supply and hydropower generation. Within the main watershed of Xining City, increasing urbanization results in increased runoff to streams and increased withdrawals from surface water reservoirs. Withdrawals have also been increasing as a result of growth in irrigated agriculture. A hydrologic modeling approach on a watershed scale was used to analyze the long‐term implications of these factors and to quantitatively assess the trade‐offs between water supply and food production within this semi‐arid watershed. The policy implications of the findings in a Food‐ Energy‐Water nexus framework for the region will be provided to regional decision makers to aid in future watershed management. © 2017 American Institute of Chemical Engineers Environ Prog, 37: 62–72, 2018